Sistem Informasi Pemesanan Pecel Sayur Berbasis Website - Anggun Mustika Sari; Muhamad Bahrul Ulum (Jurnal Pepadun, 2023)
The importance of information technology for customers cannot be overstated. It plays a crucial role in helping individuals streamline their work processes and access the necessary information. Hence, this study has developed a website-based ordering system for vegetable "pecel" to simplify the order placement process for customers. The system development approach adopted here follows the waterfall method. The system design utilizes UML (Unified Modeling System), and it is constructed using PHP (Hypertext Preprocessor) programming language with a MySQL database. Additionally, it incorporates GPS (Global Positioning System) for location access. During the design and implementation of the system, the researchers applied the PIECES analysis method, which comprises various aspects such as performance, information, cost-effectiveness, control, efficiency, and service. To assess the system's effectiveness, the researchers conducted Black Box Testing to evaluate its functionality.